Literature Study: The Role of Social-Emotional Intelligence in Improving Academic Achievement Among Elementary School Students - N Afiqah; Hikma Wati (PT. Lontara Digitech Indonesia, 2025)
Social-emotional intelligence is an individual’s ability to understand, manage, and utilize one’s own emotions as well as those of others. Various studies have shown that social-emotional intelligence plays an important role in improving the academic achievement of elementary school students. This study employed a literature review method by collecting and analyzing scientific journal articles from the last five years, books, and other relevant sources of information. The data were interpreted qualitatively to determine the relationship between social-emotional intelligence and the academic achievement of elementary school students. The review results showed that the majority of studies found a relationship between social-emotional intelligence and the academic achievement of elementary school students. These findings emphasize the importance of developing social-emotional intelligence among elementary school students as an effort to improve academic achievement. Practical implications include the need for interventions that focus on improving students’ emotional and social abilities in the school environment.